MODEL PREDIKSI PREVALENSI OBESITAS PADA PENDUDUK UMUR DIATAS 15 TAHUN DI INDONESIA - Ekowati Retnaningsih (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Indonesia has two malnutrition problems. They are under nutrition and over nutrition. The main malnutrition problem in old people is over nutrition that can lead to obesity problem. It influences the case of degenerative diseases. The aim of this research is to get information about the factor that related with obesity and to get information of obesity predictive model in the over 15 years old population. This research use ecology study and cross sectional design. Population are 33 provinces in Indonesia, sample is total population. It uses Riskesdas data in 2007. Data analysis use multi regression linier test. Result of this research show that obesity prevalence in Indonesia is 19,10 %. Prevalence of fat consumption have significant relation with prevalence of = 15,1 + 0,31(prevalence of fat consumption). The conclusions of this research are prevalence of fat consumption influences obesity prevalence of province population in Indonesia. The increase of fat consumption prevalence 1% cause the increase of obesity prevalence 0,31%.